1976
DOI: 10.1073/pnas.73.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Surface marker characteristics and Epstein-Barr virus studies of two established North American Burkitt's lymphoma cell lines.

Abstract: Tumor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

1977
1977
1979
1979

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…At the same time it is fair to add that the importance of these distinctions has been doubted (Dorfman, 1977). BURKITT LYMPHOMA In spite of clinical , epidemiological, immunological (Epstein et al, 1976), andvirological (Zur Hausen, 1975;Andersson et al, 1976;Ziegler et al, 1976) differences between endemic African (Burkitt, 1958) and sporadic African and non-African (O'Conor et al, 1965;Burkitt, 1967) Burkitt lymphomas, their morphological-cytological expressions are very similar (Berard et al, 1969). This tumour has been considered as the most classic example of an undifferentiated ML because of its uniform and monomorphic cellular population without evidence of maturation.…”
Section: Malignant Lymphomas Made Up Exclusively Ormentioning
confidence: 99%
“…At the same time it is fair to add that the importance of these distinctions has been doubted (Dorfman, 1977). BURKITT LYMPHOMA In spite of clinical , epidemiological, immunological (Epstein et al, 1976), andvirological (Zur Hausen, 1975;Andersson et al, 1976;Ziegler et al, 1976) differences between endemic African (Burkitt, 1958) and sporadic African and non-African (O'Conor et al, 1965;Burkitt, 1967) Burkitt lymphomas, their morphological-cytological expressions are very similar (Berard et al, 1969). This tumour has been considered as the most classic example of an undifferentiated ML because of its uniform and monomorphic cellular population without evidence of maturation.…”
Section: Malignant Lymphomas Made Up Exclusively Ormentioning
confidence: 99%
“…Ultrastructural, cytochemical, and immunologic studies of the biopsy specimens from patients with diffuse histiocytic lymphomas (DHL) have shown that although some of these malignancies appear to be truly histiocytic by virtue of their lyso- zyme and nonspecific esterase content, others bear monoclonal surface immunoglobulins or are devoid of all distinguishing characterist i c~.~,~~-~~*~~ Some investigators have thus questioned the "histiocytic" nature of these lymphomas and have postulated that they represent a heterogeneous groups of malignancies, the majority of which are derived from the B-lyrnpho~yte.~,~~ In 1974, we reported the successful establishment in continuous culture of cells from the malignant pleural and peritoneal effusions of three patients with DHL. 17 Since then, cell lines from seven additional patients with this diagnosis have been established in continuous cell culture. The neoplastic nature of the first five DHL cell linesl9 and recently of cell lines SU-DHL-6 to 10 (unpublished data) was convincingly shown by intracranial heterotransplantation in the nude, athymic mouse, and for all the cell lines by karyotypic analysis using quinacrine and Giemsa banding technique^.^^ In an attempt to characterize further the malignant cell populations from these ten DHL patients, the cell lines were studied for the presence of surface markers, Epstein-Barr virus (EBV) genomes, cytochemistry, immunoglobulin and lysozyme production, and phagocytic activity.…”
mentioning
confidence: 99%
“…In the category of lymphoblastic lymphomas all Burkitt type lymphoma cells show surface immunoglobulins in suspension (Binder et al, 1975 ;Epstein et al, 1976;Mann et al, 1976) but only a minority of these tumors actually produce and secrete immunoglobulins (Epstein, 1970;Sherr and Uhr, 1971;Van Furth et al, 1972) and this is also the experience from our immunomorphological studies. The T-cell nature of the convoluted type was assessed by spontaneous rosette formation (Lukes and Collins, 1975;Mann et al, 1975;Stein et al, 1976) and consequently immunoglobulin containing cells are missing in these neoplasms.…”
Section: Discussionmentioning
confidence: 65%